Duration and frecuency of heat waves in Northern tropical Africa from 5 thermal indexes - (:unkn) unknown (My University, 2019)
Thermal extremes generate health risks that are increasingly taken into account, including in tropical Africa. This work compares the duration and the frequency of spring heat waves (HWs) in West Africa according to 5 indices: Warm Spell (WS), Heat Index (HI) with and without the relative humidity, Apparent Temperature (AT), and Excess Heat Factor (EHF). The daily relative humidity and temperature data (minimum, maximum, dew point are provided by the GSOD database for the period 1973-2014 and cover 145 stations spread over a large African area (3-24°N; 24°W-36°E). The results show that the duration of the HWs is short on the coast (3 days) and they last longer inland the continent and in the Sahelian belt. HWs’ frequency varies greatly according to the heat indices used, from 3% of spring days in Cape Verde to 30 % in Central Sahel for the EHF.
Keywords: African Research